2014
DOI: 10.1002/2013wr014756
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium water dynamics in the rhizosphere: How mucilage affects water flow in soils

Abstract: The flow of water from soil to plant roots is controlled by the properties of the narrow region of soil close to the roots, the rhizosphere. In particular, the hydraulic properties of the rhizosphere are altered by mucilage, a polymeric gel exuded by the roots. In this paper we present experimental results and a conceptual model of water flow in unsaturated soils mixed with mucilage. A central hypothesis of the model is that the different drying/wetting rate of mucilage compared to the bulk soil results in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 35 publications
6
131
0
Order By: Relevance
“…Chia seed exudate has been widely used in other studies as a model root exudate (Ahmed et al 2014;Kroener et al 2014). It was extracted based on Naveed et al (2017) and Ahmed et al (2014) by mixing 100 g distilled water with 10 g chia seeds using a magnetic stirrer for 2 min at 50°C, followed by cooling to room temperature (20°C) and 4 h standing.…”
Section: Extraction Of Chia (Salvia Hispanica) Seed Exudatementioning
confidence: 99%
“…Chia seed exudate has been widely used in other studies as a model root exudate (Ahmed et al 2014;Kroener et al 2014). It was extracted based on Naveed et al (2017) and Ahmed et al (2014) by mixing 100 g distilled water with 10 g chia seeds using a magnetic stirrer for 2 min at 50°C, followed by cooling to room temperature (20°C) and 4 h standing.…”
Section: Extraction Of Chia (Salvia Hispanica) Seed Exudatementioning
confidence: 99%
“…The fourth would be related to organic carbon released by plant roots in the form of polymeric gel (the so-called root exudation, mucilage, or rhizodeposition) which were reported to decrease the mobility of clay colloids and enhance water retention around the roots (e.g. Grayston et al 1997;Traoré et al 2000;Kroener et al 2014;Tian et al 2015;Ghezzehei and Albalasmeh 2015). Recent work by Bengough (2012) shows that some of these root exudations exhibit hydrophobic or hydrophilic behavior, depending on the soil water content, causing the hysteretic-like behavior.…”
Section: R a F Tmentioning
confidence: 99%
“…Young [1995] came to a similar conclusion after measuring a higher water content in the rhizosphere of wheat compared to the adjacent bulk soil. Recently, Ahmed et al [2014] and Kroener et al [2014] showed that mucilage exuded by chia seeds increases the water content of a sandy soil at any water potential if the system is in hydraulic equilibrium.…”
Section: Introductionmentioning
confidence: 99%